Simultaneous beat-by-beat investigation of the effects of the Valsalva maneuver on left and right ventricular filling and the possible mechanism. - Zhen Wang (PLoS ONE, 2013)
Although the influence of the Valsalva maneuver on the heart and circulatory system has been investigated, the mechanism of intrathoracic pressure influencing cardiovascular function is unclear. To test our hypothesis that the interaction between the anatomy-determined partially-intrathoracic system and the fully-intrathoracic system might explain those issues and help to disclose the mechanism, we used the Hitachi dual pulse wave Doppler echocardiographic apparatus to investigate simultaneously the beat-by-beat influence of 40-mmHg Valsalva maneuver on left and right cardiac ventricular filling in 30 male adult volunteers. The mitral and tricuspid blood inflow velocity spectra during the Valsalva maneuver were recorded simultaneously. The peak velocity (PV), velocity-time integral (VTI) and inflow volume (IV) of each cycle were measured or calculated. The PV, VTI and IV of the left heart remained unchanged at the first beat after the Valsalva maneuver onset (compared with those at rest, p>0.1) and then decreased gradually to the lowest at the 11±1.2th beat (range, 9th to 12th beat). Simultaneously, the PV, VTI and IV of the right heart decreased significantly (p<0.05) at the first cycle, decreased rapidly to the lowest at the 6±0.8th beat (range, 4th to 7th beat) and then increased gradually to the 9±1.3th beat (range, 8th to 10th beat). These results suggest that the left heart and right heart have different physiological responses to the Valsalva maneuver. These could be explained by our hypothesis, the interaction between the partially-intrathoracic system and the fully-intrathoracic system, which might help to disclose the mechanism of how intrathoracic pressure influences the heart and circulatory system.